1991
DOI: 10.1161/01.cir.83.5.1808
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin has biological actions at pathophysiological concentrations.

Abstract: The present studies demonstrate that endothelin at pathophysiological plasma concentrations produced by exogenous endothelin has biological action. These studies support a functional role for endogenous endothelin as a potentially pathophysiological vasoconstrictor peptide hormone in the regulation of cardiovascular, renal, and endocrine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
3
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(63 citation statements)
references
References 26 publications
8
50
3
2
Order By: Relevance
“…In the present study, our selection of doses of ET-1 for systemic delivery was guided by earlier studies showing that ET-1 at 2.5 ng⅐ kg Ϫ1 ⅐min Ϫ1 reaches the pathophysiological range (4,11). Our measurements of plasma ET-1 are consistent with values reported in human (1,6,13,20,24) and animal heart failure (3,22,25).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, our selection of doses of ET-1 for systemic delivery was guided by earlier studies showing that ET-1 at 2.5 ng⅐ kg Ϫ1 ⅐min Ϫ1 reaches the pathophysiological range (4,11). Our measurements of plasma ET-1 are consistent with values reported in human (1,6,13,20,24) and animal heart failure (3,22,25).…”
Section: Discussionsupporting
confidence: 80%
“…However, these studies lead to apparently opposite results: in vitro ET-1 The purpose of the present study was to determine the relationship between the renin-angioteninvariably suppresses renin secretion, 13,14 while injection of ET-1 into animals does not either effect sin-aldosterone system and plasma ET-1 levels in hypertensive patients with low, normal and highor increase PRA. 11,12,26 In healthy human volunteers, infusion of 0.4 pmol/kg/min ET-1, which elevated renin essential hypertension. The data that emerged from our study demonstrated that in patients with ir-ET-1 to levels similar to those found in several pathological conditions, increased diastolic BP, low-renin essential hypertension, the plasma ET-1 potentiates the angiotensin II-induced production of aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is involved in maintaining basal RBF in the late gestation ovine fetus (Bogaert, Kogan & Mevorach, 1993). Endothelin 1 (ET-1) is implicated in modulating peripheral vascular tone during normoxia and during acute hypoxia in the sheep fetus (Green, McGarrigle, Bennet & Hanson, 1995) and ET-1 constricts afferent arterioles in the adult rabbit kidney in vitro (Ito, Juncos, Nushiro, Johnson & Carretero, 1991) and increases RVR in the adult dog in vivo (Lerman, Hildebrand, Aarhus & Burnett, 1991). Endothelin-1 binding sites have been located in the human fetal renal blood vessels in greater quantities than in the adult (Grone, Laue & Fuchs, 1990) and ETA receptor subtypes have been implicated in the maintenance of baseline renal vascular tone in the adult rat (Pollock & Opgenorth, 1993).…”
Section: Blood Gases and Phmentioning
confidence: 99%